Magnetic states of the two-leg-ladder alkali metal iron selenides AFe2Se3 - Luo, Qinlong (2013)
Recent neutron scattering experiments addressing the magnetic state of the two-leg-ladder selenide compound BaFe2Se3 have unveiled a dominant spin arrangement involving ferromagnetically ordered 2×2 iron superblocks, that are antiferromagnetically coupled among them (the ``block-AFM''state). Using the electronic five-orbital Hubbard model first-principles techniques to calculate the electronic hopping amplitudes between irons, and the real-space Hartree-Fock approximation to handle the many-body effects, here it is shown that the exotic block-AFM state is indeed stable at realistic electronic densities close to n∼6.0. Another state with parallel spins along the rungs and antiparallel along the legs of the ladders (the “CX” state) is close in energy. This state becomes stable in other portions of the phase diagrams, such as with hole doping, as also found experimentally via neutron scattering applied to KFe2Se3. In addition, the present study unveils other competing magnetic phases that could be experimentally stabilized by varying either n chemically or the electronic bandwidth by pressure. Similar results were obtained using two-orbital models, studied here via Lanczos and density-matrix renormalization group (DMRG) techniques. A comparison of the results obtained with the realistic selenides hopping amplitudes for BaFe2Se3 against those found using the hopping amplitudes for pnictides reveals several qualitative similarities, particularly at intermediate and large Hubbard couplings.